Elaborating Conflict in Maluku Based on Dialogical Liberative Perspective - Muhammad, Iqtamar; Alfian, Andi (LP2M UIN Sunan Kalijaga, 2022)
The conflict in Maluku is one of the largest religious conflicts that has ever occurred in Indonesia. This study aims to elaborate the relationship between conflict in Maluku and interreligious and cultural dialogue based on a dialogical-liberative perspective. By using the library research method, relying on books and journals related to research questions, this study attempts to discuss forms of interreligious dialogue and pre- and post-conflict culture in Maluku with a liberative dialogue approach. This study argues that liberative dialogue is a relevant approach for inter-religious dialogue in Maluku. The results of this study indicate that liberative dialogue can be an alternative for elaborating the conflict in Maluku. [Konflik di Maluku adalah salah satu konflik agama terbesar yang pernah terjadi di Indonesia. Penelitian ini bertujuan untuk mengelaborasi relasi antara konflik di Maluku dengan dialog antaragama dan budaya berdasar pada perspektif dialogis-liberatif. Dengan menggunakan pendekatan library reseach, dengan mengandalkan buku-buku dan jurnal yang berkaitan dengan pertanyaan-pertanyaan penelitian, penelitian ini berusaha mendiskusikan bentuk-bentuk dialog antarumat beragama dan budaya pra dan pasca konflik di Maluku dengan pendekatan dialog liberatif. Penelitian ini berargumentasi bahwa dialog liberatif adalah pendekatan yang relevan bagi dialog antar agama di Maluku. Hasil penelitian ini menunjukkan bahwa dialog liberatif bisa menjadi alternatif untuk mengelaborasi konflik di Maluku.]